The role of torso stiffness and prediction in the biomechanics of anxiety: a narrative review - Seong Chin (Frontiers Media S.A., 2024)
Although anxiety is a common psychological condition, its symptoms are related to a cardiopulmonary strain which can cause palpitation, dyspnea, dizziness, and syncope. Severe anxiety can be disabling and lead to cardiac events such as those seen in Takotsubo cardiomyopathy. Since torso stiffness is a stress response to unpredictable situations or unexpected outcomes, studying the biomechanics behind it may provide a better understanding of the pathophysiology of anxiety on circulation, especially on venous impedance. Any degree of torso stiffness related to anxiety would limit venous return, which in turn drops cardiac output because the heart can pump only what it receives. Various methods and habits used to relieve stress seem to reduce torso stiffness. Humans are large obligatory bipedal upright primates and thus need to use the torso carefully for smooth upright activities with an accurate prediction. The upright nature of human activity itself seems to contribute to anxiety due to the needed torso stiffness using the very unstable spine. Proper planning of actions with an accurate prediction of outcomes of self and non-self would be critical to achieving motor control and ventilation in bipedal activities. Many conditions linked to prediction errors are likely to cause various degrees of torso stiffness due to incomplete learning and unsatisfactory execution of actions, which will ultimately contribute to anxiety. Modifying environmental factors to improve predictability seems to be an important step in treating anxiety. The benefit of playful aerobic activity and proper breathing on anxiety may be from the modulation of torso stiffness and enhancement of central circulation resulting in prevention of the negative effect on the cardiopulmonary system.